Pengaruh Pemahaman Akuntansi, Tingkat Pendidikan dan Skala Usaha Terhadap Penerapan Penyusunan Laporan Keuangan pada UMKM: Studi kasus UMKM di Kecamatan Banyumas - Devie Oktavianita; Giovanny Bangun Kristianto; Esti Saraswati (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to determine the influence of accounting understanding, education level, and business scale on the implementation of financial reporting in UMKM in Banyumas District, both partially and simultaneously. The study population comprised all UMKM in Banyumas District. The sampling technique used purposive sampling. The sample size was 143 respondents, calculated using the Slovin formula and meeting several predetermined criteria. Data collection used a questionnaire. The results indicate that accounting understanding, education level, and business scale simultaneously influence the implementation of financial reporting in UMKM. Accounting understanding partially influences the implementation of financial reporting in UMKM. Education level partially influences the implementation of financial reporting in UMKM. Business scale partially influences the implementation of financial reporting in UMKM.